2014
DOI: 10.1107/s1600577513032402
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, optimization and surface physics aspects ofin situplasma mirror cleaning

Abstract: Although the graphitic carbon contamination of synchrotron beamline optics has been an obvious problem for several decades, the basic mechanisms underlying the contamination process as well as the cleaning/remediation strategies are not understood and the corresponding cleaning procedures are still under development. In this study an analysis of remediation strategies all based on in situ low-pressure RF plasma cleaning approaches is reported, including a quantitative determination of the optimum process param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 19 publications
2
18
3
Order By: Relevance
“…In the same vein and following previous studies (Gonzá lez Cuxart et al, 2016;Pellegrin et al, 2014;Moreno Ferná ndez et al, 2018), the ICP-type ibss model GV10x low-pressure plasma source together with N 2 /O 2 /H 2 and N 2 /H 2 feedstock gases have been used to clean Ni, Rh and Al foil materials and ultrathin Al filters for EUV applications.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…In the same vein and following previous studies (Gonzá lez Cuxart et al, 2016;Pellegrin et al, 2014;Moreno Ferná ndez et al, 2018), the ICP-type ibss model GV10x low-pressure plasma source together with N 2 /O 2 /H 2 and N 2 /H 2 feedstock gases have been used to clean Ni, Rh and Al foil materials and ultrathin Al filters for EUV applications.…”
Section: Introductionmentioning
confidence: 83%
“…A set of Ni, Rh and Al metal foils with micrometric thickness were contaminated with 50 nm of amorphous carbon (a-C) using electron beam deposition inside a commercial deposition setup together with high-purity polycrystalline graphitic carbon targets (Pellegrin et al, 2014) for simulating a photon-beam induced carbon contamination ( Fig. 1).…”
Section: Materials and Cleaning Test Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…They also measured the cleaning rates of carbon allotropes by varying the RF power and the distance between source and object. Pellegrin et al (2014) used a capacitively coupled RF plasma system for the study of carbon cleaning rates from a quartz crystal microbalance. They observed that the carbon cleaning rate increases with increasing RF power and oxygen gas flow rate, but they did not measure the surface properties of the crystal after plasma cleaning.…”
Section: Introductionmentioning
confidence: 99%
“…In order to refurbish the contaminated optics to pristine efficiency, different groups have suggested and applied several online and offline cleaning techniques (UV/O 3 cleaning, RF plasma cleaning, in-situ cleaning in beam lines by Oxygen activated by synchrotron radiations, etc.) [10,[12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%